2005
DOI: 10.1128/jb.187.5.1710-1715.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Core Lipopolysaccharide ofEscherichia coliIs a Ligand for the Dendritic-Cell-Specific Intercellular Adhesion Molecule Nonintegrin CD209 Receptor

Abstract: The dendritic-cell-specific intercellular adhesion molecule nonintegrin (DC-SIGN) CD209 is a receptor for Escherichia coli K-12 that promotes bacterial adherence and phagocytosis. However, the ligand of E. coli for DC-SIGN has not yet been identified. In this study, we found that DC-SIGN did not mediate the phagocytosis of several pathogenic strains of E. coli, including enteropathogenic E. coli, enterohemorrhagic E. coli, enterotoxigenic E. coli, and uropathogenic E. coli, in dendritic cells or HeLa cells exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
121
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(133 citation statements)
references
References 40 publications
10
121
0
2
Order By: Relevance
“…1) The core LPS of E. coli mediates the interaction with DC-SIGN. Our previous data (13) and Fig. 3 confirm that the waaR mutant does not interact with DC-SIGN as well as its parent strain CS180, suggesting that it is the core LPS rather than other components on the E. coli surfaces interacting with DC-SIGN.…”
Section: Examination Of the Interaction Of Core Lps Mutants Of E Colsupporting
confidence: 62%
See 4 more Smart Citations
“…1) The core LPS of E. coli mediates the interaction with DC-SIGN. Our previous data (13) and Fig. 3 confirm that the waaR mutant does not interact with DC-SIGN as well as its parent strain CS180, suggesting that it is the core LPS rather than other components on the E. coli surfaces interacting with DC-SIGN.…”
Section: Examination Of the Interaction Of Core Lps Mutants Of E Colsupporting
confidence: 62%
“…1) from Neisseria gonorrhoeae (GC) in both DCs and HeLa cells expressing human DC-SIGN Ag (HeLa-DC-SIGN) (12). We further demonstrated that it is the core LPS region of E. coli that interacts with DC-SIGN (13).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 86%
See 3 more Smart Citations